The Legal Implications for Citizenship Status of Mixed Marriages Registered at The Office of Religious Affairs - Muhammad Aminuddin Shofi; Imam Bayhaki; Muhammad Masdar Umaruddin (Sekolah Tinggi Agama Islam Miftahul Ulum Lumajang, 2025)
Married couples of different nationalities must have a thorough understanding of the Religious Affairs Office's mixed marriage registration process because it has significant legal ramifications for the future of the family, including joint property ownership and the citizenship status of the children. This study looks at how mixed marriages are handled administratively at the Religious Affairs Office in Gumukmas District, Jember Regency, and considers the legal implications for citizenship status. A case study and legal approach are used in this empirical legal research, and interviews and documentation are used as data collection methods. The data is then subjected to a number of analysis techniques, including data editing, classification, verification, and analysis, before being presented in a succinct, clear, and straightforward but still engaging conclusion narrative. The findings of the study indicate that the Office of Religious Affairs is authorized to offer mixed marriage registration services in accordance with Minister of Religious Affairs Regulation Number 24 of 2024, subject to a number of administrative constraints. A permit from the appropriate Embassy, a Certificate of No Impediment, also known as a single letter, a copy of the passport, and, in the event that the foreign national's country of origin is unrelated, all documentation must be translated into Indonesian are additional requirements for mixed marriages. Because mixed marriages can result in such complicated legal implications, the Office of Religious Affairs' marriage registrars have a specific and urgent duty to educate prospective brides and grooms about the significance of the administrative process. Mixed marriages have legal implications for both husband and wife since they provide them the option to keep their individual citizenships or adopt their partner's citizenship. The citizenship status of children from mixed marriages is also affected; for example, children from mixed marriages retain dual citizenship until they turn 18 until they choose to adopt their mother's or father's citizenship.